2017
DOI: 10.4269/ajtmh.16-0482
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E in Singapore: A Case-Series and Viral Phylodynamics Study

Abstract: Abstract. The incidence of hepatitis E in Singapore appears to be increasing. A retrospective case-series study of patients diagnosed with hepatitis E in a tertiary hospital from 2009 to 2013 was conducted. Of 16 cases, eight (50%) were solid-organ transplant recipients (SOTRs), and 14 (88%) were found infected by genotype 3 hepatitis E virus (HEV-3). Bayesian inferences based on HEV subgenomic sequences from seven cases suggest that HEV-3 strains were introduced to Singapore as two principal lineages. Within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 42 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…A small minority of HEV genotype 3 strains were from the 3efg clade (4/59, 7%; Figure a). Of these strains, two sequences shared the same ancestor as a genotype 3e strain from Japan (3e_Sw_Japan_AB248521) while two others belonged to the same lineage as that of a previously reported strain in Singapore (KT447527) which was believed to have originated from the United States (Teo et al, ). All but four genotype 3 strains were from Chinese persons—two genotype 3a strains were detected from Indian individuals, one strain was from a Caucasian and one was from an individual of unknown race.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…A small minority of HEV genotype 3 strains were from the 3efg clade (4/59, 7%; Figure a). Of these strains, two sequences shared the same ancestor as a genotype 3e strain from Japan (3e_Sw_Japan_AB248521) while two others belonged to the same lineage as that of a previously reported strain in Singapore (KT447527) which was believed to have originated from the United States (Teo et al, ). All but four genotype 3 strains were from Chinese persons—two genotype 3a strains were detected from Indian individuals, one strain was from a Caucasian and one was from an individual of unknown race.…”
Section: Resultsmentioning
confidence: 84%
“…Molecular analyses of sequences in our study of human sera revealed genotype 3 to be distinctly the most prevalent (121/143, 84.6%), with genotype 3a as the main circulating strain. Although Teo et al () and Zhu et al () have previously described the identification of genotype 3a in Singapore, the number of their cases (3 and 15, respectively) was small. Our study detected genotype 3a in 44 of 59 patient samples with concatenated ORF1 and ORF2 sequences (74.6%).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations